Ownership concentration, dividend payout and firm performance: The case of Malaysia - Ting I.W.K.; Kweh Q.L.; Somosundaram K. (Malaysian Economic Association, 2023)
This study examines how ownership concentration affects dividend payout, and ultimately firm performance. Regression analyses are performed on a dataset spanning 11 years (2005-2015) among Malaysian publicly listed firms. The results show that shareholders with concentrated ownership play an important role in determining dividend payout and driving firm performance. Specifically, ownership concentration is associated with low dividend payout, but it improves firm performance. Overall, this study suggests that ownership concentration may also be an effective monitoring mechanism.